2017
DOI: 10.32468/be.1020
|View full text |Cite
|
Sign up to set email alerts
|

Impacto del crédito sobre el agro en Colombia : evidencia del nuevo Censo Nacional Agropecuario

Abstract: ResumenEste trabajo utiliza, por primera vez, los microdatos del Censo Nacional Agropecuario del 2014 para evaluar el impacto del otorgamiento de crédito en el sector agropecuario. A través de un análisis de Propensity Score Matching, se estudia el efecto en algunas variables que son de interés para los formuladores de políticas públicas, entre ellas el rendimiento de la finca, medido en toneladas de producción por hectárea, y elÍndice de Pobreza Multidimensional (IPM).En general, los resultados sugieren que l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
0
5
0
1
Order By: Relevance
“…Depending upon the source of the credit, impacts on yields ranged from 6% to 24% (Echavarría et al, 2018). Considering that public information did not include the specific features of the programs involved in implementation of the peace agreement and that such programs could affect several crops simultaneously, we assumed a conservative increase in total factor productivity of 4% in our simulations.…”
Section: Application and Resultsmentioning
confidence: 99%
“…Depending upon the source of the credit, impacts on yields ranged from 6% to 24% (Echavarría et al, 2018). Considering that public information did not include the specific features of the programs involved in implementation of the peace agreement and that such programs could affect several crops simultaneously, we assumed a conservative increase in total factor productivity of 4% in our simulations.…”
Section: Application and Resultsmentioning
confidence: 99%
“…• Total factor productivity: We model the subsidy to cover the interest rate and financial costs and expenses associated with agricultural credit operations as an increase in total factor productivity (Echavarría, Villamizar-Villegas, Restrepo-Tamayo, and Hernández-Leal, 2018). According to our calculations, this policy would have an impact of 6% on the total factor productivity.…”
Section: Methodsmentioning
confidence: 99%
“…Higher access to credit is associated with higher growth rates in the agricultural sector (Hartarska et al, 2015). For the Colombian case, Echavarría-Soto, Villamizar-Villegas, Restrepo-Tamayo, Hernández-Leal, and Echavarría (2017) found that access to credit has significant effects on agricultural production and poverty reduction. Then, municipalities with more access to credit might report a higher (more negative) decrease in coca crops due to more investment capacity.…”
Section: Heterogeneous Effectsmentioning
confidence: 98%